Lifecycle cost optimization of vibration mitigation in rotating machinery: Integrating measured transmissibility, finite element modeling, and downtime cost scenarios - Mohammad, Sulieman Ibrahim; Maashari, Naeema Darwish Khamis Al; Vasudevan, Asokan; Wu, Wenya; Hunitie, Mohammad Faleh Ahmmad; Mohammad, Anber Abraheem Shlash; Al-Fawwaz, Torki M. (Sound & Vibration, 2026)
Rotation devices play a vital role in industrial plants, where vibrations significantly affect efficiency, reliability, and the overall cost of operation. Vibrations cause wear and tear, failures, and high maintenance time, but previous studies have focused on machine efficiency without including financial factors. This paper provides a solution to this problem by developing an integrated approach to optimizing lifetime cost through vibration reduction in rotation devices. A numerical approach was used to quantify and analyse the phenomenon, including experimental measurement, finite element (FE) modelling, and economic analysis. Transmissibility measurement was used to describe vibration dynamics and validate the FE model. The response of the system was correlated to wear and tear, failure rates, and downtime. These factors were then used to formulate a lifetime cost model. The results have shown that there is a strong non-linear connection between the transmissibility factor and the lifecycle cost, where the higher the levels of vibrations, the greater the extent of wear and tear and downtime. The process of optimizing identified the optimum operating point where there is a perfect compromise between the vibration performance and the cost effectiveness. The sensitivity analysis has revealed that the transmissibility is the most significant factor affecting the lifecycle cost.